Conventional radiograph and cone-beam computed tomography in the evaluation of odontogenic cysts and tumors - An analysis of seven cases - Durgadevi Boopathi; Jimsha Vannathan Kumaran; Srinivasan Subramanian Vasudevan; Jonathan Daniel Mariappan (Wolters Kluwer Medknow Publications, 2020)
Introduction: Odontogenic cysts and tumors are the most common pathologies affecting the jaws. Radiographic evaluation of cysts and tumors is an important aspect of diagnosis and surgical treatment planning. Cone-beam computed tomography (CBCT) provides three-dimensional views of cysts and tumors regarding accuracy and quality of interpretation. Aim and Objective: The aim of the study is to determine the radiographic features of odontogenic cysts and tumors in conventional radiograph and in CBCT and to assess the advantages of CBCT over conventional radiography in the evaluation of cysts and tumors. Materials and Methods: All types of odontogenic cysts and tumors in both males and females were included. Nonodontogenic cysts and tumors were excluded. Conventional radiograph and cone-beam computed tomographic images of seven patients who had histopathologically confirmed odontogenic cysts and tumors were retrospectively reviewed from the archives of the department of oral medicine and radiology in the institution. Conclusion: In this radiographic study, the advantages of CBCT in the assessment of extent, effect on surrounding structures and internal structure of odontogenic cysts and tumors were determined, and specific advantages of CBCT were ascertained.